Testing the use of the Prioritee Decision Support Tool in Portugal Towards Descarbonised Public Buildings - Silva, Raquel Ourives da (2023)
In the European region, more specifically in the Mediterranean area, most of the public authorities need to enhance their institutional capacity in the field of Energy Efficiency (EE) and use of Renewable Energy Sources (RES) to contribute to the Energy Performance of Buildings and the Energy Efficiency Directives, developing solutions adapted to various regional contexts. In the national context, there is a clear pressure for energy independence and decarbonization, which inevitably pass through the in- crease of ambition regarding the target for Energy Efficiency. The work developed within this dissertation focuses on the collection and application data be- longing to the buildings of LNEG (State Laboratory of Energy and Geology), Arruda dos Vinhos Munic- ipality, and AREANATejo (Regional Energy and Environment Agency). For this analysis, 22 public build- ings were selected to identify the priority interventions to improve energy efficiency and optimize energy uses, evaluating their effectiveness in terms of energy savings, reduction in CO2 emissions, and return on in-vestment (ROI). The goal, after testing the tool, was to support the definition of a local action plan that could support the drafting of the city’s Sustainable Energy and Climate Action Plan. This study is framed with the follow-up project – PrioritEE PLUS, recently funded by INTERREG MED, whose focus is the testing of the PrioritEE Decision Support Tool (DST). The data to be inserted in this tool comes from the buildings' Energy Performance Certificates, encompassing a diversity of end users from local authorities. Given the results of the prioritization analysis of improvement measures suggested by the DST, the most recommended renovations to be implemented, resulting from the savings felt by the decision makers as well as from the energy performance of the buildings, are the substitution of the floors, as well as the replacement of the windows. The results allow to understand which type of buildings have more energy performance deficien- cies within the clusters under analysis and, through this sample, to give municipalities this sectorial knowledge to integrate into their Energy and Climate Action Plans, which in many situations is required to apply for funds and funding.